A COMPARATIVE STUDY OF ICT STOOL ANTIGEN, SERUM AND ELISA TECHNIQUES IN DETECTION OF HELICOBACTER PYLORI AMONG SUDANESE FOOD HANDLER (Journal of Universal Science Research, 2024)
Background: Helicobacter pylori (H. pylori) remains one of the most common human infections in Sudan recently and is associated with a number of important chronic gastritis, peptic ulcer disease and gastric malignancy. Objectives: The aim of this study was to compare the detection of H. pylori IgG in serum using ELISA techniques compared to ICT blood test and stool antigen. Materials and Methods: Stool and blood specimens were collected from 100 patients (mean age 31.2 ± 11.7 years, 56% males). Stool samples were analyzed using rapid stool antigen test for H. pylori and Serum samples were analyzed for H. pylori IgG by Accurate© (USA) ELISA and ICT blood test. Data analysis was made by the software of the Statistical Package for Social Sciences (SPSS) program (version 22). Results: The incidence of H. pylori among male was 12/17 (71%) compare to 5/17 (29%) females. 17 (17%) patients have positive with rapidstoolAg ICT test compare to 20 (20%) patients have positive by H. pylori IgG ELISA [the Accurate© (USA)]. The sensitivity, specificity, positive predictive value and negative predictive value for H. pylori IgG ELISA were (100%, 96.1%, 93.3% and 100% respectively) compared to ICTH. pylori IgG for blood (41.18%, 71.08%, 43.4% and 69.2% respectively) using rapid stool Ag ICT test as gold standard method.  Conclusion:  The  better results Sensitivity and Specificity obtained for H. Pylori diagnosis wasH. pylori IgG using ELISA techniques compared to ICT blood test.